Performa Kambing yang Diberi Kulit Buah Kakao Terfermentasi - Suparjo Suparjo; K G Wiryawan; E B Laconi; D Mangunwidjaja (Faculty of Animal Science, Bogor Agricultural University, 2011)
Utilization of cocoa pod husk (CPH) as feedstuff needs pretreatment to increase its nutrients availability. Bioconversion with Phanerochaete chrysosporium changes its structure by breaking down the linkage between lignin and structural carbohydrates. This experiment was aimed to evaluate the quality of fermented CPH biomass as feed for goats. The experimental treatments i.e.: A= 30% of fresh napier grass (RG) + 50% of dried RG + 20% of concentrate; B= 30% of fresh RG + 30% of dried RG + 40% of concentrate; C= 30% of fresh RG + 30% of CPH + 40% of concentrate; D= 30% of fresh RG + 30% of fermented CPH + 40% of concentrate and E= 30% of fresh RG + 50% of fermented CPH + 20% of concentrate. The treatments were allocated in a randomized block design with three replications. Feed intake, body weight gain and ration efficiency were measured. The use of fermented CPH at the level of 30% had higher (P < 0.05) feed intake (560.33 g day-1), body weight gain (101.79 g head-1 day-1), and feed conversion (5.50) compared to other treatments. In conclusion that the use of 30% fermented CPH in the ration showed the best body weight gain and feed efficiency.